Stiffness of Vascular Smooth Muscle Cells from Monkeys Studied using Atomic Force Microscopy - Zhu, Yi (Cardiology and Cardiovascular Medicine, 2021)
Vascular smooth muscle cells (VSMC) are the main cellular components of blood vessel walls and bear external mechanical forces caused by blood flow and pressure. In this report, we have verified the following hypothesis through experiments: The increase in VSMC stiffness may be mainly due to changes in vascular stiffness due to aging. Although aging enhances the stiffness and adhesion of VSMC, there is no significant difference in apparent elastic modulus and adhesion between the VSMC obtained by male and female. The effect of aging through the ECM-integrin-cytoskeleton axis is related to increased VSMC stiffness and matrix adhesion rather than gender.